Blood fibrinogen as a biomarker of chronic obstructive pulmonary disease. Issue 7 (28th June 2012) - Duvoix, Annelyse; Dickens, Jenny; Haq, Imran; Mannino, David; Miller, Bruce; Tal-Singer, Ruth; Lomas, David A
Abstract : Background: Chronic obstructive pulmonary disease (COPD) is a multicomponent condition that is characterised by airflow obstruction that is not fully reversible and is a major global cause of morbidity and mortality. The most widely used marker of disease severity and progression is FEV1 . However, FEV1 correlates poorly with both symptoms and other measures of disease progression and thus there is an urgent need for other biological markers to better characterise individuals with COPD. Fibrinogen is an acute phase plasma protein that has emerged as a promising biomarker in COPD. Here we review the current clinical evidence linking fibrinogen with COPD and its associated co-morbidities and discuss its potential utility as a biomarker. Methods: Searches for appropriate studies were undertaken on PubMed using search terms fibrinogen, COPD, emphysema, chronic bronchitis, FEV1, cardiovascular disease, exacerbation and mortality. Results: There is strong evidence of an association between fibrinogen and the presence of COPD, the presence and frequency of exacerbations and with mortality. Fibrinogen is associated with disease severity but does not predict lung function decline, a measure used as a surrogate for disease activity. The role of fibrinogen in identifying inflammatory co morbidities, particularly cardiovascular disease, remains unclear. Fibrinogen is reduced by p38 mitogen-activated protein kinase inhibitors in individuals with stable disease and by oral corticosteroids during exacerbations. Conclusions: Fibrinogen is likely to be a useful biomarker to stratify individuals with COPD into those with a high or low risk of future exacerbations and may identify those with a higher risk of mortality.